2016
DOI: 10.3390/app6120355
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Drag Reduction Phenomenon within a Rotating Disk Apparatus Using Polymer-Surfactant Additives

Abstract: Pipelines and tubes play important roles in transporting economic liquids, such as water, petroleum derivatives, and crude oil. However, turbulence reduces the initial flow rate at which liquids are pumped, thereby making liquid transportation through pipelines inefficient. This study focuses on enhancing the drag reduction (DR) phenomenon within a rotating disk apparatus (RDA) using polymer-surfactant additives. The complex mixture of polyisobutylene (PIB) and sodium dioctyl sulfosuccinate (SDS) was used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This will lead to higher costs. Musaabet al [45] studied the drag reduction efficacy of Sodium Di-octylsulfosuccinate (SDS), Sodium dodecyl benzene sulfate (SDBS), and Sodium lauryl ether sulfate (SLES) with diesel fuel in a rotating disk apparatus is investigated, the result showed that the maximum drag reduction achieved was 29.5% for Sodium lauryl ether sulfate (SLES) at 1100 RPM and 1000 ppm.…”
Section: Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will lead to higher costs. Musaabet al [45] studied the drag reduction efficacy of Sodium Di-octylsulfosuccinate (SDS), Sodium dodecyl benzene sulfate (SDBS), and Sodium lauryl ether sulfate (SLES) with diesel fuel in a rotating disk apparatus is investigated, the result showed that the maximum drag reduction achieved was 29.5% for Sodium lauryl ether sulfate (SLES) at 1100 RPM and 1000 ppm.…”
Section: Surfactantsmentioning
confidence: 99%
“…Table 1 summarizes the previous studies regarding the usage of various drag reducing agents in crude oil pipes and in water as a fluid. 50%DR at 20ppm poly(ethylene oxide) (PEO) water Figueredo and Sabadini [18] 40%DR at 30ppm Polyalpha-olefin (Polyisobutylene) Crude oil Mowla and Naderi [29] 55.58%DR at 250ppm coconut fiber Water Marmy et al [6] 25%DR at 50ppm nata de coco fiber water Warashina and Ogata [38] 50%DR Carbon Nanotubes (CNT) with Xanthan gum (XG) water Akindoyo et al [4] 29.5%DR at 1000ppm Sodium laurylether sulfate (SLES) water Musaab et al [45] 38%DR at 300ppm Al2O3nanoparticles water Yanuar et al (…”
Section: Nanomaterialsmentioning
confidence: 99%
“…27 This new drag reducer features a low molecular weight, a fastdissolving rate, and low interfacial tension, and the SPR DR rate calculated by the Fanning friction coefficient exceeded 60%. Rashed et al 28 used a complex mixture of polyisobutylene, and sodium dioctyl sulfosuccinate (SDS) was used to enhance the DR phenomenon. Abdulbari et al 29 also found that the addition of a tiny amount of surfactant to the polymer system resulted in a significant improvement compared to the pure polymer DR.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of polymeric DRAs in the transported solutions is in the form of networks and clusters depending on the polymer solubility and the polarity. The molecular weight, polarity, and morphology of the DRA polymer will control the size, shape, and distribution of these clusters in the fluid core and on the conduit's solid surface [15,16]. It is believed that the characteristics of these clusters strongly control the drag reduction phenomena and stability of the polymeric DRAs.…”
Section: Introductionmentioning
confidence: 99%